Mating system in Myracrodruon urundeuva (Anarcadiaceae): implications for conservation genetics - Gaino,Ana Paula Silva Campos (2011)
The aims of this study were to investigate the mating system of a fragmented population of the dioecious tropical tree Myracrodruon urundeuva Allemão, using five microsatellite loci and the mixed mating and correlated mating models. The study was conducted in the Estação Ecológica de Paulo de Farias (436 ha), where the population occupies about 142 ha. The mating system was estimated using 514 open-pollinated offspring, collected from 30 seed-trees. Estimates of the multilocus outcrossing rate confirm that the species is dioecious (t m = 1.0). Low levels of mating among relatives were detected in the population (1 - t s = 0.020). The estimate of paternity correlation (r p(m)) indicated that offsprings were composed of mixtures of half-sibs and full-sibs, with the latter occurring at a low frequency (average of 0.148). The estimated coancestry coefficient within families (Θ = 0.147) was larger and the effective population size (Ne(v)) was lower (Ne(v) = 2.98) than expected in progenies from panmictic populations (Θ = 0.125, Ne(v) = 4, respectively). In terms of conservation, the results indicate that to retain an effective population size of 150, is necessary to collect seeds from at least 50 seed-trees.